Exploring EFL Students’ Perspectives Towards Google Docs in Writing - Hafidhah Khansa Asih; Putu Dian Danayanti Degeng; Hamamah Hamamah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
During an online learning environment, students organize and develop their ideas in writing using Google Docs, and they hold their online consultation through the comment section. The research aims to explore students’ perspectives towards Google Docs in writing classes. A survey method using a quantitative approach was employed to collect data for this research. The researcher composed a questionnaire consisting of 17 questions and an interview as the instrument of this research to explore EFL students’ perspectives regarding Google Docs and distributed it to 24 students in a Seminar on ELT D of the English Language Education Program at Universitas Brawijaya. After processing the findings of the questionnaire using SPSS ver. 25.0, the researcher found that the students of the Seminar on ELT D project had a positive perspective towards Google Docs in writing class. As an alternate writing tool in online learning, Google Docs can be useful to students. However, students prefer using face-to-face for consultation or employing synchronous learning, such as video conferencing, to assist students in better grasping how to develop and arrange their thoughts.